A critical approach to humanizing pedagogies in online teaching and learning. Issue 3 (12th April 2020) - Mehta, Rohit; Aguilera, Earl
Abstract : Purpose: In this paper, the authors draw on theories of critical pedagogy to interrogate recent trends in online education scholarship, calling for more humanizing pedagogies. By using vignettes from their own teaching experiences, the paper illustrates tensions between autonomous and ideological visions of humanizing approaches, particularly how they apply to issues of inclusion in online teaching and learning. Design/methodology/approach: The authors draw on critical theory to interrogate the framings of humanizing online teaching. Sharing three illustrative vignettes from their own reflexive teaching practice, the authors demonstrate how a critically framed approach to humanizing digital pedagogies can promote the design and enactment of more inclusive learning environments across online contexts. Findings: Based on the pedagogical cases presented, the authors demonstrate (1) how methods promoted in autonomous models of humanizing pedagogy can present challenges for inclusive design, (2) how participatory media production activities can still intersect with issues of racialization, and (3) how humanizing pedagogical commitments by individual instructors can be constrained by material, structural, and institutional realities. Practical implications: While critical framings of pedagogy necessarily resist prescriptive recommendations, the authors conclude the article by underscoring the importance of critically interrogating the ideological dimensions of humanizing pedagogies, the need to grapple with social inequities even as educational contexts are increasingly digitized; the importance of considering structural issues of power and privilege that produce and constrain pedagogical possibilities. Originality/value: The authors offer a critical framing of humanizing pedagogies in online education that runs counter to the often-autonomous framings of these approaches, highlighting issues of power, privilege, and ideology that can be overlooked in online educational contexts, especially at the level of institutional, instructional design and support.